Reliability model and proposed maintainability activities of earth station system - Abdul Rahim, Nadirah; Nordin, Nor'Afifah (Institute for Technology and Research, 2020)
Earth station system plays a big role in communications industry. To ensure that the earth station system functioning throughout specified period of time, the reliability and maintainability of the system needs to be analyzed. This paper presents the analysis on the reliability of 2-parallel and 3-parallel configurations of earth station system with Mean Time Between Failure of 6 months, 2.5 years, 3.7 years, 4.5 years and 5 years using secondary data obtained from Monte Carlo generator in Matlab. A new reliability model is created based on the results obtained. Suitable maintenance activities are also proposed for the earth station system.